Uso de automedicación y medicina natural ante SARS-CoV-2 en hogares de estudiantes de medicina - Sanchez Vargas, Danny Anndre (2021)
Due the impact of the COVID-19 pandemic, the lack of information, the limitations of the health system and the fear constantly generated, many of the population took various measures to treat themselves. In this descriptive and cross-sectional study, we sought to describe the use of self-medication and/or natural medicine to face a possible SARS-CoV- 2 infection in the homes of medical students. For this, a virtual survey was conducted between the months of May and October 2020 in the homes of FMUNT medical students. The survey had 13 questions to determine characteristics and demographic data about participants, and 14 questions to describe the characteristics of self-medication practice and treatment with medicinal plants. Of the 244 households taken into account, in 132, (54.1%) they self-medicated and in 87, (36.5%) they treated themselves with medicinal plants. The main reason for resorting to these practices was to consider the symptoms presented to be mild. The most commonly consumed drugs were paracetamol (84.9%), NSAIDs (40.9%).The most consumed medicinal plants were eucalyptus (77%), lemon (60.9%) and kion (55.2%).We concluded that the prevalence of these practices in the homes of medical students was significant, especially self-medication, which is why we recommend emphasizing the risks that may be associated with the inadequate administration of these drugs.